2019
DOI: 10.1093/gerona/glz201
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer-Measured Sleep Duration and Clinical Cardiovascular Risk Factor Scores in Older Women

Abstract: Background Evidence suggests that short and long sleep durations are potential lifestyle factors associated with cardiovascular disease (CVD). Research on sleep duration and CVD risk is limited by use of self-report sleep measures, homogeneous populations, and studies on individual CVD risk factors. For women, risk of CVD and inadequate sleep duration increases with age. We hypothesized that accelerometer-measured sleep duration was associated with 10-year predicted probability of future CVD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Despite its close relationships with both mental health and physical activity, sleep has been largely overlooked in the literature for physical activity in relation to mental health. Currently, sleep duration can be accurately measured with ecological sampling approaches such as wrist-worn accelerometers, which have been adopted in medical and mental health research [30,31]. At the neural network level, sleep deprivation has been linked to a reduction in functional connectivity within the DMN [32][33][34], whereas increased sleep duration has been linked to strengthened connectivity within the DMN but reduced connectivity between DMN and SN [35].…”
Section: Potential Overlap Between Mental Health and Physical Activit...mentioning
confidence: 99%
“…Despite its close relationships with both mental health and physical activity, sleep has been largely overlooked in the literature for physical activity in relation to mental health. Currently, sleep duration can be accurately measured with ecological sampling approaches such as wrist-worn accelerometers, which have been adopted in medical and mental health research [30,31]. At the neural network level, sleep deprivation has been linked to a reduction in functional connectivity within the DMN [32][33][34], whereas increased sleep duration has been linked to strengthened connectivity within the DMN but reduced connectivity between DMN and SN [35].…”
Section: Potential Overlap Between Mental Health and Physical Activit...mentioning
confidence: 99%
“…Additionally, although sleep might not be considered a type of physical activity for its inactive nature, it is closely connected to mental health such that sleep problems have been considered as a risk factor for subsequent development of depressive symptoms 37,38 , and disrupted sleep is often seen in patients with various types of mood and anxiety disorders [39][40][41] . Sleep duration can be accurately measured with ecological sampling approaches such as wrist-worn accelerometers, which have been adopted in medical and mental health research 42,43 .…”
Section: Neural Correlates Of Physical Activitymentioning
confidence: 99%
“…Although sleep has been largely overlooked in the literature for physical activity in relation to mental health, we included it in the current study for its close relationships with both mental health and physical activity. Sleep duration can be accurately measured with ecological sampling approaches such as wrist-worn accelerometers, which have been adopted in medical and mental health research 30,31 . At the neural network level, sleep deprivation has been linked to reduction in functional connectivity within the DMN [32][33][34] , whereas increased sleep duration has been linked to strengthened connectivity within the DMN but reduced connectivity between DMN and SN 35 .…”
Section: Potential Overlap Between Mental Health and Physical Activit...mentioning
confidence: 99%
See 1 more Smart Citation
“…There were few and inconsistent reports on how sleep duration affects health outcomes in young individuals who do not yet have chronic diseases. Some studies suggested a U -shaped association between sleep duration and suboptimal SRH ( 13 ), and others suggested that only short sleep is associated with suboptimal SRH ( 14 ). To the best of our knowledge, previous studies have not controlled for confounding effect of circadian rhythm-related factors such as chronotype, daytime napping, snacking after dinner.…”
Section: Introductionmentioning
confidence: 99%